Analysis of Sopi Farmers' Income Levels (in Negeri Soya RT/02 RW/007 Ambon City) - Soplanit, Rian Ayos; Papilaya, Josef; Sahusilawane, Stevie (Universitas Pattimura, 2025)
This study aims to analyze the income levels of sopi farmers in Negeri Soya, Ambon, and the factors influencing them. Primary data were obtained through interviews with active sopi producers, while secondary data were sourced from various literature. The results show that weekly sopi production ranges from 7 to 14 jerry cans, with each can having a capacity of 5 liters. Weather conditions and farmers' fermentation skills significantly affect production volumes. In terms of income, farmers earn between Rp 5,000,000 and Rp 6,000,000 per month, depending on production volume and selling prices. Operating costs, especially for fuel and equipment, also affect the net profits. In conclusion, although production is relatively small-scale, sopi farming provides significant income for local farmers. The study recommends the use of simple technology and infrastructure support to enhance production stability and market access.